ANALISIS PENGARUH PENDAPATAN BUNGA KREDIT DAN BIAYA BUNGA DANA PIHAK KETIGA TERHADAP LABA BERSIH PADA BANK OCBC NISP PERIODE 2012-2018 - Loeky Rono Pradopo (Jurnal Manajemen dan Bisnis Jayakarta, 2020)
This research aims to find out the effect of loans interest income and interest expenses of third party funds on the net income of Bank OCBC NISP for the period of 2012-2018. The variables examined in this research are independent variables, among others, loans interest income and interest expenses of third party funds and the dependent variable used is net income. This research uses bank OCBC NISP financial report data for the period 2012-2018. The analysis technique uses multiple linear regression analysis and hypothesis analysis uses the t-test and F-test. Other analysis uses classical assumptions with normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The conclusion of this research describes that based on statistics result, loans interest income and interest costs of third party funds simultaneously/together has a significant effect on net profit. This is evidenced by the value of R2 in this research that is equal to 0.972 or 97.2 %, which means that 97.2 % of profit is influenced by loans interest income and interest costs on third party funds and 2.8 % is influenced by other factors not listed in this research. Based on this, it is recommended that Bank OCBC NISP increase the production of lending, increase the collection of low-expenses funds, and reduce operational expenses to obtain profits according to management's expectations